Criminology: theory, research, and policy - Vito, Gennaro F. (Criminal justice illuminated, 2007)
Crime and criminology -- The incidence of crime -- Neoclassical criminology -- Biology and crime -- Psychology and crime -- Social structure and crime -- Social process and crime -- Social conflict and crime -- Crime and criminal careers -- Crimes of violence -- Emerging forms of violence -- Property crimes -- Public order crimes -- Drugs and crime -- Crimes of the powerful -- The future of criminal justice and criminology.